Human body - Gabb, Michael H.; Forsey, Christopher (New York : Kingfisher Books, 1992)
Examines the complex machinery that is the human body and analyzes how it fulfills its function in carrying out our everyday activities.
Originally published: New York : Warwick Press, 1991.
Includes index.
Keywords: Human body -- Juvenile literature; Human physiology -- Juvenile literature; Human body; Human physiology